2017
DOI: 10.1159/000478277
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes and Associated Risk Factors of Post-Hospitalization Dialysis-Dependent Acute Kidney Injury Patients

Abstract: Background/Aims: Acute kidney injury requiring dialysis (AKI-D) is associated with poor outcomes. Centers for Medicare and Medicaid Services have reversed their clarification allowing AKI-D patients to be dialyzed at outpatient dialysis units. Data assessing long-term outcomes of AKI-D patients and their predictors is needed to adopt guidelines to ensure adequate management. We assessed long-term outcomes and associated risk factors of AKI-D patients who survived 90 days post-hemodialysis (HD) initiation. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Iram et al [3] reported that 4.35% of their AKI patients died and CKD developed in 28.69%. There are similar reports about this subject in the literature [4][5][6].…”
Section: Introductionsupporting
confidence: 56%
“…Iram et al [3] reported that 4.35% of their AKI patients died and CKD developed in 28.69%. There are similar reports about this subject in the literature [4][5][6].…”
Section: Introductionsupporting
confidence: 56%
“…A recent study showed that patients with eGFR ≥ 30 mL/min/1.73 m 2 had a significantly higher likelihood of kidney function recovery, even after adjustment for intensive care unit (ICU) initiation, catheter access, sepsis/postoperative etiology of AKI, acute tubular necrosis and heart failure (HR, 5.86, p < 0.001) [21]. Researchers at the university of Virginia evaluated outcomes of patients with AKI-D following their hospital discharge, and showed that patients with baseline eGFR <45 mL/min are 88% less likely to achieve dialysisindependence, both short-term [7] and long-term [25]. Similar studies further highlighted the effect of baseline renal function on kidney function recovery [21,24,26].…”
Section: Pre-existing Ckdmentioning
confidence: 99%
“…Second, most clinicians may find it difficult to change the definition AKI into AKD after 7 days, when confronted with patients who need dialysis beyond 1 week, or even up to 3 months after the start of AKI [96][97][98].…”
Section: The Concept Of Akd and Its Interrelationship With Aki And Ckdmentioning
confidence: 99%